Ultrastable Hydroxyapatite/Titanium‐Dioxide‐Supported Gold Nanocatalyst with Strong Metal–Support Interaction for Carbon Monoxide Oxidation. Issue 36 (27th July 2016) - Tang, Hailian; Liu, Fei; Wei, Jiake; Qiao, Botao; Zhao, Kunfeng; Su, Yang; Jin, Changzi; Li, Lin; Liu, Jingyue (Jimmy); Wang, Junhu; Zhang, Tao
Abstract: Supported Au nanocatalysts have attracted intensive interest because of their unique catalytic properties. Their poor thermal stability, however, presents a major barrier to the practical applications. Here we report an ultrastable Au nanocatalyst by localizing the Au nanoparticles (NPs) in the interfacial regions between the TiO2 and hydroxyapatite. This unique configuration makes the Au NP surface partially encapsulated due to the strong metal–support interaction and partially exposed and accessible by the reaction molecules. The strong interaction helps stabilizing the Au NPs while the partially exposed Au NP surface provides the active sites for reactions. Such a catalyst not only demonstrated excellent sintering resistance with high activity after calcination at 800 °C but also showed excellent durability that outperforms a commercial three‐way catalyst in a simulated practical testing, suggesting great potential for practical applications. Abstract : Partially covered and supported : An ultrastable gold nanocatalyst was prepared by tuning the strong metal–support interaction between Au nanoparticles (NPs) and a titanium dioxide–hydroxyapatite (HAP) support (see picture). The Au NPs are located at the interfaces of TiO2 /HAP support, forming anchored and partially covered active Au NPs.